Akuntansi untuk Budgeting dan Menabung untuk Tujuan Tertentu - Mega Adhelia; Gracelina Oktavia Simanjuntak; Suci Rantiandini; Raghib Assirjani; Irenne Putren (Abdimisi, 2025)
Many high school students still face difficulties in managing their pocket money due to the lack of financial planning habits such as budgeting and goal-oriented saving. Most students tend to spend money impulsively without keeping records, resulting in imbalanced income and expenses. This situation indicates a low level of financial literacy among adolescents. 2) The main problem identified in this program is the lack of understanding of basic accounting concepts related to personal financial management, especially in budgeting and determining spending priorities. Consequently, students often find it challenging to differentiate between needs and wants. 3) The purpose of this community service activity is to improve students’ awareness and understanding of financial management through simple accounting approaches and to encourage consistent saving habits with specific goals. 4) The method used was interactive socialization through PowerPoint presentations and simple budgeting case simulations. 5) The results show that the students demonstrated higher motivation and awareness in managing their finances, recording expenses, and making proportional allocations of pocket money. 6) This activity successfully fosters positive financial habits among students that support discipline, self-control, and long-term financial responsibility. Keywords: budgeting; basic accounting; financial literacy; saving motivation